Valdemar 2. Sejr, Matthew Paris og den engelske invasionsfrygt, 1240-41 - Kjær, Lars (Historisk Tidsskrift, 2018)
Valdemar II, Matthew Paris and the rumours of a Danish invasion, 1240–41 In 1240, the English chronicler Matthew Paris recorded rumours in England that suggested the Danes were preparing to invade the kingdom. In fact, the suspected invasion travelled eastward. Matthew Paris was not, however, put at ease. In 1241 he recorded the death of Valdemar II, whom he alleged had been boasting of his right to the English throne and his plans to conquer England. This article investigates Matthew Paris’ story, and his knowledge of medieval Denmark and attitudes towards England in medieval Denmark. Matthew had not himself been to Denmark, but had access to informants with personal experience of the Danish royal court: three English clerks and artisans who had served under Valdemar II before returning to England c. 1237 and, in the case of the clerk Nicholas of St Albans, finding service in the English royal court. Matthew Paris seems not to have been alone in his anxieties about the intentions of Valdemar II. In 1240, King Henry III of England sent two separate missions to acquire more intelligence about the situation in Denmark. They must have brought back reassuring news, for English sources give no indication of preparations against invasion in the following years. Both English and Danish sources indicate that it is unlikely that an actual invasion force had been made ready in 1240. Danish sources do, however, show that Matthew’s information about the Danish boasts about their rights to the English crown are likely to have had a factual basis. In the Gesta Danorum, Saxo Grammaticus makes much of the Danish kings’ rights to the English crown. These claims were also incorporated into the hagiographical literature and liturgy for St. Knud IV. Knýtlinga saga, whose author had been part of Valdemar II’s court, also made much of them. The lost overlordship of England continued to play a role in the historical imagination of the Danish elite long into the thirteenth century.